STATUTUL ŞTIINŢELOR EDUCAŢIEI (Sinteză) - USM ADMIN (Moldova State University, 2007)
This study emphasizes the education sciences status and its analysis from a historical and epistemological perspective. It has mainly in sight the delimitation between the authentic education sciences (developed from the basis matrix of pe- dagogy) and the non authentic education sciences, appeared only as applications to education of the other social sciences. The status of pedagogy as a social science is proved by the emphasizes of the object of specific study (education, studied at a global and profound level with the help of the function and basis structure concepts and the other concepts: finality, content, general forms system and education process, specific research methodology - historical and hermeneu- tical, specific normatively expressed through axioms, laws and principles and rules. The education sciences classification values two criteria: the position towards research object, education and the research methodology mainly used. The first criteria emphasize the importance of the fundamental sciences of education: education general theory, education general teaching theory, education general curriculum theory, pedagogical research theory. The second criteria emphasize the appearance of the education sciences through different methodologies typo- logical separated. This is a perfect issue to understand the fundamental sciences of education.